Extension for Community Healthcare Outcomes (ECHO) Telementoring in the Military: Where We Are Now, Opportunities and Challenges. Issue 9 (28th August 2021) - Katzman, Joanna; Tomedi, Laura; Swift, Robin; Castillo, Erick; Morrow, Connie; Lutz, Laurie; Galloway, Kevin T; McCoy-Stafford, Kimberly; Klein, Zachary; Turner, Greg; Beckman, Darrick J; Terrell, Jennifer; et al.
ABSTRACT: Introduction: In collaboration with the ECHO (Extension for Community Healthcare Outcomes) Institute since 2012, the Army, Navy, and Air Force have developed medical teleECHO programs to address various health and safety issues affecting military personnel. This article describes and compares the current state of military teleECHOs as well as the growth and change over time. Materials and Methods: This study evaluated continuing education units (CEUs) offered, average session attendance, and number of spoke sites for current military teleECHO programs across the service branches. Results: Between 2012 and 2019, the military teleECHO initiative grew from one program to seven different teleECHO programs, covering topics from pain to diabetes to amputee care. Military ECHOs now provide training to 10 countries and 27 states in the United States. Between October 2018 and September 2019, the military ECHO programs provided a total of 51, 769 continuing medical education (CME) hours to a total of 3, 575 attendees from 223 spoke sites. Conclusions: The military has successfully used the ECHO model to improve the health and safety of active-duty military, retirees, and dependents.